Computational Fluid Dynamics Simulations of Ammonia Catalytic Crackers in OpenFOAM - Hashmi, Rameez (My University, 2025)
Ammonia is widely recognised as a promising hydrogen carrier, but efficient catalytic decomposition is required to release hydrogen for clean energy applications. This thesis investigates the catalytic cracking of ammonia through computational fluid dynamics (CFD) simulations. A one-dimensional (1D) plug-flow reactor model was implemented in OpenFOAM and validated against an equivalent Cantera simulation to ensure correct kinetic representation. A more detailed two-dimensional (2D) axisymmetric CFD model of a tubular ammonia cracker was then developed in OpenFOAM to capture radial gradients and transport phenomena. Kinetic mechanisms for ammonia decomposition on ruthenium and nickel catalysts were examined, and the Ru-based mechanism was selected for the 1D/2D simulations in OpenFOAM. The 2D model incorporates multicomponent diffusion and thermal diffusion (Soret effect), enabling it to resolve concentration and temperature gradients neglected by the 1D model. Comparison of 1D and 2D results indicates that the idealised 1D approach slightly overestimates ammonia conversion, whereas the 2D model predicts lower conversion due to pronounced radial gradients. Inclusion of mixture-averaged diffusion and the Soret effect further shapes species and temperature fields, driving hydrogen towards cooler regions and influencing local reaction rates.
Keywords: ammonia decomposition, CFD, OpenFOAM, catalytic reactor, multicomponent diffusion, thermal diffusion, Cantera